Valuation of market uncertainties for contaminated land - Bartke, Stephan (International Journal of Strategic Property Management, 2012)
The revitalization of contaminated land carries many risks and uncertainties. This paper aims to reveal drivers of risk perception and to introduce a novel valuation method for the assessment of market-perceived risks for sites polluted by earlier use in a transparent and comprehensible procedure. International approaches to account for value deductions due to contaminations and resulting uncertainties are reviewed. Based on literature review and a national survey amongst German professional appraisers, a risk assessment methodology is elaborated, outlined and applied in a case study approach. We find that areas that have been properly decontaminated on average still have a depressed market value of 12.25%. Quantities such as location, time and feasibility of passing on risks can be combined in an algorithm to determine the absolute value reduction for a specific property to be appraised. Results should help appraisers, international investors and portfolio managers to deepen their understanding of valuation of risks associated with (previously) contaminated land. First Publish Online: 11 Jan 2012